Problematic digital use among migrant adolescents in Türkiye: A PISA 2022 analysis of risk and protective factors - Morgül, Evren (Addicta: The Turkish Journal on Addictions, 2026)
This study examined the demographic, social-behavioural, and psychosocial determinants of problematic digital use among migrant adolescents in Türkiye using data from the PISA 2022 migration subsample. The sample included 7,137 first- and second-generation migrant students. Problematic digital use was measured using students’ self-reports about their digital habits, while bullying experiences, perceptions of school safety, weekend digital activity, and levels of teacher support, family support, and emotional control were assessed through established background questionnaire scales. Analyses included t-tests, correlations, and hierarchical binary logistic regression. Results showed that males and older students reported significantly higher levels of problematic digital use. Problematic use was positively associated with bullying, perceived lack of school safety, and intensive weekend digital activity, and negatively associated with teacher support, family support, and emotional control. The regression model explained 22.8% of the variance, with weekend digital use emerging as the strongest risk factor and emotional control as the strongest protective factor. Overall, the study findings show that problematic digital engagement among migrant adolescents reflects an interplay of social stressors and self-regulatory resources. Interventions targeting both emotional regulation and supportive school-family environments may help promote healthier digital behaviours in this migrant population.